Analysis of Teacher Views on the Advantages and Disadvantages (Frankenstein Syndrome) of Using Humanoid Robots in Education - Köksalan, Bahadır; Akpınar, Burhan; Akyıldız, Taha Yasin (Cahit AYDEMİR, 2024)
The advancement of humanoid robots as stakeholders in education in developed countries may soon be reflected in the Turkish Education System as a technological phenomenon of the 21st century. The progression of this reflection will be determined by teachers’ perceptions and attitudes. Therefore, it is important to understand teachers’ views on the subject. The aim of this research, driven by this importance, is to identify and analyze teacher views on the use of humanoid robots in education and the Frankenstein syndrome, considering various variables. The survey model research was conducted on a total of 1075 teachers working in public schools. Data were collected via a questionnaire and analyzed using descriptive statistical techniques. The analysis revealed that even though participating teachers may have limited knowledge about humanoid robots, they hold dualistic views, both positive and negative, on the subject. Teachers perceive the function of humanoid robots, which they partially find beneficial in education, as assisting the teacher. Teachers who reject humanoid robots replacing teachers identify their disadvantages as limiting communication, mechanizing teaching, and compromising student privacy. Teachers’ views on humanoid robots vary according to demographic variables. Finally, although teachers find the idea of humanoid robots becoming autonomous (Frankenstein syndrome) frightening, they believe it is unsettling for humanity and education, even if they do not fully understand it. The research emphasizes that this fear, originating from Western culture, should not hinder the integration of 21st-century technologies into the Turkish Education System, and underscores that the real concern should be the misuse of science leading to roboticized humans.

Gelişmiş ülkelerde eğitimin paydaşı olma yolunda ilerleyen insansı robotların, 21. Yüzyılın teknolojik olgusu olarak yakın gelecekte Türk Eğitim Sistemine de yansıması öngörülebilir. Bu yansımanın gidişatını, öğretmenlerin algı ve tutumları belirleyecektir. Bu itibarla, öğretmenlerin konu ile ilgili görüşlerinin bilinmesi, önemlidir. Bu önemden hareket eden araştırmanın amacı, eğitimde insansı robot kullanımı ve Frankeştayn sendromuna dair öğretmen görüşlerini belirleyip, çeşitli değişkenlere göre analiz etmektir. Tarama modelinde yürütülen araştırma, kamu okullarında görev yapan toplam 1075 öğretmen üzerinde yürütülmüştür. Veriler, anket formu ile toplanmış olup, betimsel istatistiki tekniklerle analiz edilmiştir. Analizler sonucunda, katılımcı öğretmenlerin, insansı robotlar hakkında fazlaca bilgi sahibi olmasalar da, konuyla ilgili olumlu ve olumsuz olmak üzere, düalist görüşlere sahip oldukları belirlenmiştir. Öğretmenler, eğitimde kısmen faydalı gördükleri insansı robotların işlevini ise, öğretmene yardımcı olmak, şeklinde görmektedirler. İnsansı robotların öğretmenin yerine geçmesini reddeden bu öğretmenlere göre bunların dezavantajları, iletişimi sınırlandırma, öğretimi mekanikleştirme, öğrenci mahremiyetini zedeleme şeklindedir. Öğretmenlerin insansı robotlar hakkındaki görüşleri, demografik değişkenlere göre farklılık göstermektedir. Son olarak öğretmenler, insansı robotların kontrolden çıkarak özerk hale gelmesini (Frankeştayn sendromu), fazla bilmeseler de, bunu, insanlık ve eğitim adına korkutucu bulmuşlardır. Araştırmada, Batı kültürü kaynaklı bu korkunun, Türk Eğitim Sisteminin 21. Yüzyıl teknolojilerine entegrasyonuna ket vurmaması gerektiğine dikkat çekilmiş ve asıl korkulması gerekenin de, bilimi yanlış kullanan, robotlaşmış insanlar olması gerektiği vurgulanmıştır.
Eğitimde İnsansı Robot Kullanımının Avantaj ve Dezavantajlarına (Frankeştayn Sendromu) Dair Öğretmen Görüşlerinin Analizi
Keywords: Curriculum Development in Education; Eğitimde Program Geliştirme